Management strategies for quarantine and invasive weeds - Saha, Sanjoy; Vijayakmar, S; Subramanian, E; Ramesh, Kulasekaran; Thirumalaikumar, R (Indian Farming, 2024)
Due to invasive / noxious weed species, enormous losses have occurred in terms of quantity and quality of crop output, loss of native biodiversity, threats to the environment, and human health. The various approaches used to control these weed species are still insufficient. To combat the invasion of non-native weed species, actions such as creating early-warning systems, increasing invasive species control, quarantining alien species, and raising public awareness are required. Preventing weed invasion using a combination of strategies focused on reducing encroachment is the most effective method for managing invasive weeds. Thus, there is an urgent need to strengthen integrated weed management approaches against invasive and quarantine weeds across the country.